PENGARUH PENERAPAN METODE WEBQUAL 4.0 PADA KEPUASAN PENGGUNA WEBSITE BURSA KERJA KHUSUS (BKK) SMK NEGERI 2 SURABAYA - Satria, Brama Seta Putra; Iswati (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
This research explores the significance of SMK Negeri 2 Surabaya's Special Employment Exchange (BKK) website as a valuable support system for students entering the workforce. By digitizing and enhancing the BKK website using the WebQual 4.0 method, the study aims to improve user experience and Quality for job-seeking students. The main objectives include evaluating user satisfaction with the BKK website based on WebQual 4.0 and analyzing the factors that impact the website 's Quality for job searching. The findings revealed that 62% of respondents were highly satisfied and 34% were moderately satisfied with the BKK website . Among the factors influencing user satisfaction, Content (CON) played the most significant role, achieving a satisfaction level of 68.1%, followed by Service Interaction Quality (SIQ) at 22.9%, Usability Quality (USQ) at 8.2%, and Information Quality (INQ) at -12.7%. Overall, the combined variables in the model influenced user satisfaction by 63.9%.